MULTICULTURAL PEDAGOGY BASED ON CULTURAL AWARENESS IN REMOTE SCHOOLS OF KALIMANTAN - Maemonah Maemonah; Inggit Dyaning Wijayanti; Anita Ekantini; Abroto Abroto (Program Studi PGSD Universitas Flores, 2025)
Indonesia’s cultural and ethnic diversity in schools requires teachers to develop strong pedagogical competencies that foster cultural awareness. This study aims to (1) conduct sociocultural pedagogy socialization using a cultural awareness model for teachers at SDS Eka Cipta Kencana, (2) provide assistance in implementing multicultural pedagogy within classroom practices, and (3) evaluate the effectiveness of the socialization and assistance activities. The research employed a qualitative community-based research (CBR) design involving 13 teachers and 261 students, with data collected through interviews, observations, and documentation. Data were validated using source and technique triangulation to ensure credibility. The results show that multicultural pedagogy at SDS Eka Cipta Kencana has not been fully integrated into the formal curriculum but is implicitly practiced through teachers’ personal approaches that embrace local cultural contexts. Socialization and mentoring activities enhanced teachers’ understanding of multicultural pedagogy and fostered tolerance among students of diverse backgrounds. Rather than being confined to structured lessons, cultural awareness emerged through everyday interactions that validated students’ diverse identities. This suggests that in remote schools, diversity is not merely a backdrop but an active force that shapes more inclusive and humane forms of education. This study contributes to strengthening pedagogical practices in remote schools by offering a model of multicultural pedagogy grounded in cultural awareness that can inform future teacher development programs.